2010
DOI: 10.1177/1077546310373617
|View full text |Cite
|
Sign up to set email alerts
|

Model, tests and application design for viscoelastic dampers

Abstract: Many kinds of dampers are invented to reduce the dynamic responses due to earthquake or strong wind. Viscoelastic damper is a kind of commonly used passive control device for vibration mitigation of structures. Its energy dissipation characteristics are affected by environmental temperature and excitation frequency. In order to describe the complex characteristics of viscoelastic dampers changing with temperature and frequency, a new model — the equivalent standard solid model, which is based on the standard l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 9 publications
0
56
0
Order By: Relevance
“…All of the hysteretic loops are obviously plump, which indicates that the VE dampers can efficiently dissipate energy. Compared with the VE dampers described in previous studies , the maximum damping force of this type of VE damper is greater, which means that the energy dissipation capacity is also larger. More significantly, the ultimate strain is remarkably greater.…”
Section: Performance Tests Of Viscoelastic Dampermentioning
confidence: 58%
See 1 more Smart Citation
“…All of the hysteretic loops are obviously plump, which indicates that the VE dampers can efficiently dissipate energy. Compared with the VE dampers described in previous studies , the maximum damping force of this type of VE damper is greater, which means that the energy dissipation capacity is also larger. More significantly, the ultimate strain is remarkably greater.…”
Section: Performance Tests Of Viscoelastic Dampermentioning
confidence: 58%
“…In general, the damper behavior is nearly independent of frequency and is less insusceptible to velocity. This feature is very different from other types of VE dampers and will be significant in seismic application, because the damper behavior remains stable when the structural frequency is increased by the additional stiffness provided by the VE damper.…”
Section: Performance Tests Of Viscoelastic Dampermentioning
confidence: 88%
“…Xu et al examined the performance of an eight‐story–reinforced concrete frame structure with installed VE dampers using numerical simulations. It was concluded that VE dampers have good energy dissipation capacity, which leads to a significant increase in structural stiffness and damping.…”
Section: Introductionmentioning
confidence: 99%
“…And how to accurately calculate or simulate the mechanical properties of viscoelastic materials is a complex problem (Lewandowski and Chorazyczewski, 2010). A large number of scholars have studied viscoelastic materials and put forward a series of mechanical models, including Maxwell model, Kelvin model, standard solid model (Kim et al, 2003), ESS (equivalent standard solid) model (Xu, 2007;Xu et al, 2011), equivalent stiffness and equivalent damping model (Yoshida et al, 2002), fractional derivative model (Xu et al, 2015), Finite element model, complex stiffness model, Standard rheological model (Mould et al, 2011;Lee and Choi, 2018), fractional index model (Gonzalez et al, 2016;Chen et al, 2018), micro-oscillator model (Mctavish and Hughes, 1993), and so on. The ESS model is a new computational model based on temperature frequency equivalent principle and standard linear solid model, which can correctly describe the variation of viscoelastic damper with the change of temperature and frequency.…”
Section: Introductionmentioning
confidence: 99%